Research integration using dialogue methods - McDonald, David (Free online access: OAPEN., 2009)
Research on real-world problems--like restoration of wetlands, the needs of the elderly, effective disaster response and the future of the airline industry--requires expert knowledge from a range of disciplines, as well as from stakeholders affected by the problem and those in a position to do something about it. This book charts new territory in taking a systematic approach to research integration using dialogue methods to bring together multiple perspectives. It links specific dialogue methods to particular research integration tasks. Fourteen dialogue methods for research integration are classified into two groups: 1. Dialogue methods for understanding a problem broadly: integrating judgements 2. Dialogue methods for understanding particular aspects of a problem: integrating visions, world views, interests and values. The methods are illustrated by case studies from four research areas: the environment, public health, security and technological innovation.